2022
DOI: 10.1002/adfm.202206696
|View full text |Cite
|
Sign up to set email alerts
|

A Room Temperature Route toward In Situ Crystallization of Perovskite Nanocrystals Induced by Acrylic Acid for Flexible Free‐Standing Luminescent Gels

Abstract: Perovskite nanocrystals (PNCs) with unique and excellent optical properties have emerged as appealing luminescent materials in optoelectronic fields. However, high temperature processing, complicated procedures, and the use of toxic solvents are typically involved in the preparation of PNCs and their related optoelectronic devices. In this study, a one‐step method is developed for the preparation of flexible photoluminescence gel based on PNCs at ambient conditions, which is a promising alternative to the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Low levels of the polymer (1-5 wt.% or 0.5-5 mg mL −1 ) enhance the PLQY due to surface defect passivation and improve the PeLEDs in terms of operational stability [37,38] while higher polymer percentages result in higher PeLED efficiencies (EQE). [13,30] In all published works, although the role of the polymer percentage in controlling nucleation and growth of MHPs grains has been suggested [39] the detailed interaction mechanism is not fully understood due to the chemical complexity of the solution containing the MHPs precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of the polymer (1-5 wt.% or 0.5-5 mg mL −1 ) enhance the PLQY due to surface defect passivation and improve the PeLEDs in terms of operational stability [37,38] while higher polymer percentages result in higher PeLED efficiencies (EQE). [13,30] In all published works, although the role of the polymer percentage in controlling nucleation and growth of MHPs grains has been suggested [39] the detailed interaction mechanism is not fully understood due to the chemical complexity of the solution containing the MHPs precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, combined with a 3D printing technique, it is able to customize LSCs with a variety of shapes for different applications. [142,149] It is noteworthy that structure optimization is an efficient way to reduce self-absorption loss and thus increase quantum yield. In literature, it is frequently reported that NCs can be optimized into core-shell heterojunction structures to solve the reabsorption problem.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…6,7 With high PL, excellent color purity, and a wide color gamut, PNCs are also highly attractive for high-definition displays. [8][9][10] The PNC-LEDs can fully meet the requirements of the highdefinition luminous displays specified by REC.2020. 11 Moreover, recent breakthroughs have pushed the external quantum efficiency (EQE) of PNC-LEDs to new heights, surpassing 25% for green and red-light LEDs, and exceeding 10% for blue-light LEDs.…”
Section: Introductionmentioning
confidence: 99%